Interlinked credit, relational contracting, and the spread of rural-based manufacturing the case of garment and metalcraft industries in the Philippines - Briones, Roehlano M. (The Philippine Review of Business and Economics, 2002)
Subcontracting arrangements based on relational contracting between urban traders and rural-based manufacturers provide an important means for spreading manufacturing in rural areas. Within these arrangements, the payment of advances is a form of credit interlinking that addresses the isolation of rural-based enterprises from the formal finance sector. This viewpoint motivates specification of a testable hypothesis: advance payments are greater the more remote a rural-based subcontractor is from the urban center. The paper shows that such a hypothesis can be derived from a simple principal-agent model of the subcontracting relation. Moreover, the hypothesis is empirically confirmed by multivariate analysis of data from a case study of garment and metalcraft industries in the Philippines. The finding supports the view that subcontracting arrangements may be an organizational form appropriate to rural industrialization.